The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Desalination 2014
DOI: 10.1002/9781118904855.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Humidification Dehumidification Desalination

Abstract: Humidification-dehumidification (HDH) desalination involves vaporizing water from a saline liquid stream into a carrier gas stream and then condensing the vapor to form purified water. This chapter describes various forms of the HDH cycle, with analysis of the energy consumption of various realizations of the process. The use of mass extraction/injection to improve performance is discussed. Analyses using both fixed component effectiveness and fixed component size are considered. Bubble column dehumidifiers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 82 publications
0
15
0
1
Order By: Relevance
“…It firstly enters the humidifier to get heated and humidified by the hot seawater (process 3-4). Then it is directed to the dehumidifier, where it is cooled down by the feed seawater (stream 6) and the moisture content is condensed (4)(5). The distillate (stream 10) is collected as the product water, while the preheated seawater is further heated using external heat sources (stream 11) before being sprayed into the humidifier.…”
Section: Process Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It firstly enters the humidifier to get heated and humidified by the hot seawater (process 3-4). Then it is directed to the dehumidifier, where it is cooled down by the feed seawater (stream 6) and the moisture content is condensed (4)(5). The distillate (stream 10) is collected as the product water, while the preheated seawater is further heated using external heat sources (stream 11) before being sprayed into the humidifier.…”
Section: Process Descriptionmentioning
confidence: 99%
“…It has a low operation temperature (50-70 ℃), simple system components, easy maintenance and operation, and low initial plant costs. These advantages distinguish HDH from other desalination processes, making it suitable for integration with renewable energy sources [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although it does not compete with existing technologies for desalinating seawater in medium and large scale applications, HDH can be advantageous in decentralized, off-grid desalination applications where fresh water demand ranges up to several thousand cubic meters per day [1,2]. In addition, the technology does not use membranes and does not include hot metal surfaces, which allows it to treat highly saline water with some oil content without requiring expensive corrosion resistant metals.…”
Section: Introductionmentioning
confidence: 99%
“…Narayan et al [17] and Mistry et al [18] showed that the top water temperature and mass flow rate ratio of air and water streams play a major role in identifying the maximum GOR in an HDH system. Some of the existing HDH thermal desalination technologies were discussed by Narayan et al [19]. Some of the HDH systems discussed in their study were multi-stage air heated cycle, mechanical compression driven cycle, HDH with thermodynamic balancing, HDH with common heat transfer wall, and hybrid HDH system with reverse osmosis, among others.…”
Section: Introductionmentioning
confidence: 99%